S33 Vitamin D and airway remodelling in paediatric severe therapy resistant asthma. (2nd December 2011) - Sjoukes, A; Gupta, A; Oates, T; Bush, A; Saglani, S
Abstract : Background: Serum vitamin D levels have been related to asthma control and medication use in children with mild to moderate disease, but little is known about the relationship between serum vitamin D levels and airway remodelling and mucosal inflammation in asthma. We hypothesised that lower serum vitamin D levels would be associated with increased airway inflammation and remodelling and lower lung function in children with severe therapy resistant asthma (STRA). Methods: Nineteen children aged between 6 and 16 years with STRA underwent spirometry, fiberoptic bronchoscopy, endobronchial biopsy, and measurement of serum vitamin D (25(OH)D3 nmol/l). Endobronchial biopsies stained with H&E were used to quantify airway remodelling (reticular basement membrane thickness, smooth muscle mass and epithelial shedding). Immunohistochemistry was used to quantify smooth muscle cell proliferation using proliferating cell nuclear antigen, and inflammatory cells (eosinophils, neutrophils and mast cells). Results: Seventeen of 19 children with STRA were vitamin D insufficient (<50 nmol/l), median (range) serum 25(OH)D3 29 (21–39) nmol/l. There was no relationship between serum 25(OH)D3 and submucosal eosinophils, neutrophils or mast cells. Airway smooth muscle mass was inversely related to serum 25(OH)D3 (r=−0.6, p=0.007) (Abstract S33 figure 1 ), but there was no relationship between vitamin D levels and reticular basement membrane thickness or epithelial shedding. Lung function was not related to serum vitamin D levels, however bronchodilator reversibility was inversely related to serum 25(OH)D3 levels (r=−0.53, p=0.02). Conclusions: Vitamin D insufficiency is common in children with STRA. Lower vitamin D levels in children with STRA were associated with increased airway smooth muscle and increased bronchodilator reversibility. Randomised controlled trials of vitamin D supplementation are warranted in paediatric STRA.